Quercetin in Oncology: A Phytochemical with Immense Therapeutic Potential - Kamal, Raj; Paul, Priyanka; Thakur, Shubham; Singh, Sachin Kumar; Awasthi, Ankit (Current Drug Targets, 2024)
Quercetin is a natural flavonoid with various pharmacological actions such as anti-inflammatory, antioxidant, antimicrobial, anticancer, antiviral, antidiabetic, cardioprotective, neuroprotective, and antiviral activities. Looking at these enormous potentials, researchers have explored how they can be used to manage numerous cancers. It's been studied for cancer management due to its anti-angiogenesis, anti-metastatic, and antiproliferative mechanisms. Despite having these proven pharmacological activities, the clinical use of quercetin is limited due to its first-pass metabolism, poor solubility, and bioavailability. To address these shortcomings, researchers have fabricated various nanocarriers-based formulations to fight cancer. The present review overshadows the pharmacological potential, mechanisms, and application of nanoformulations against different cancers.TeaserExplore the potential of Quercetin, a natural flavonoid with diverse pharmacological activities, and its nanoformulations in managing various cancers.
Keywords: Quercetin